2016
DOI: 10.1002/bmc.3668
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo metabolism studies of dimethazine

Abstract: The use of anabolic steroids is prohibited in sports. Effective control is done by monitoring their metabolites in urine samples collected from athletes. Ethical objections however restrict the use of designer steroids in human administration studies. To overcome these problems alternative in vitro and in vivo models were developed to identify metabolites and to assure a fast response by anti-doping laboratories to evolutions on the steroid market. In this study human liver microsomes and an uPA(+/+) -SCID chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Previous reports of the equine in vitro phase I metabolism of S provided some comparison with the present study . Several human in vivo and in vitro studies of S metabolism have also been reported . Metabolism of S with UDPGA, ATP, Na 2 SO 4 , and equine liver S9 fraction afforded a range of phase II sulfate and glucuronide metabolites which are summarized in Figure .…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Previous reports of the equine in vitro phase I metabolism of S provided some comparison with the present study . Several human in vivo and in vitro studies of S metabolism have also been reported . Metabolism of S with UDPGA, ATP, Na 2 SO 4 , and equine liver S9 fraction afforded a range of phase II sulfate and glucuronide metabolites which are summarized in Figure .…”
Section: Resultssupporting
confidence: 71%
“…The formation of the 3β‐hydroxy metabolites is known to be favoured in horses, and this is followed by sulfation to give major 3β‐RSS and glucuronylation to give minor 3β‐RSG . Alternatively, the tentative assignment above suggests that formation of the 3α‐hydroxy metabolite 3α‐RS is followed by glucuronylation to give major G12 but not sulfation to 3α‐RSS , in a pattern similar to that observed in humans . Although no unconjugated phase I metabolites were identified directly in this LC–MS study, the phase I metabolism of S is known to afford a number of steroid diol, and triol metabolites which ionize poorly under +ESI conditions .…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Human liver microsomes and an uPA +/+ -SCID chimeric mouse model were employed to produce its different metabolites, and the reduction in C3 together with hydroxylation in C2, C12 (minor), C16 and C20 constitute the main metabolism pathways [10,11,12]. Methasterone and its hydroxylated metabolites were also excreted as glucuronidated compounds, while no sulfated metabolites could be detected in phase II metabolism [13].…”
Section: Introductionmentioning
confidence: 99%